Foucault et la phronesis : les cas à l’épreuve de la singularité - Raphaëlle Burns (Astérion)
This article proposes to trace the presence of a discreet but continuous critical engagement with the Aristotelian category of phronesis in Foucault’s work. During the 1970s, Foucault’s research was devoted to several instances of techne, a form of practical wisdom close to, yet distinct from, phronesis. Although he hardly mentions the latter, we will show that this omission is anything but an oversight. It is through the work of phronesis and on phronesis that Foucault thinks the complexity of practical wisdom and negotiates the distinction between his own “genealogical” method and the methods that he studies. We will see that this distinction is articulated around a second doublet, that of the case and the singularity—a distinction whose meaning becomes clear once it is scrutinised through the lens of the Aristotelian triad of knowledge: episteme, techne, and phronesis. We will see that the Foucauldian notion of singularity, far from being identical to the particular case, constitutes rather its principle of internal difference. By substituting the hermeneutics of singularity for the hermeneutics of the particular, Foucault is able to articulate a renewed phronesis adapted to the present moment.